Addressing the "headwinds" faced by the European arms industry. Issue 2 (2nd April 2020) - Kleczka, Mitja; Buts, Caroline; Jegers, Marc
ABSTRACT: The European arms industry is challenged by several adverse "headwinds." Fragmentation leads to costly duplications and, in conjunction with stagnating budgets and sharply increasing costs, prevents firms from exploiting economies of scale and learning. This is exacerbated by size differentials vis-a-vis the leading US arms manufacturers and competition from emerging producers. As some "headwinds" are self-enforcing, far-reaching industrial and policy responses are required to improve the industry's outlook. As exports may not indefinitely compensate for low domestic demand, there is an economic imperative for further cross-border collaboration and consolidation. Despite various EU policy initiatives, progresses regarding the European Defence Equipment Market and strengthening the European Defence Technological Industrial Base have been relatively slow. It remains to be seen whether the European Defence Fund will be the proclaimed "game-changer, " raising competitiveness of the European arms industry. At the same time, the UK's withdrawal from the EU adds uncertainties.